Improving the recognition of post-operative acute kidney injury. Issue 1 (17th December 2014) - Trotter, Nicola; Doherty, Cal; Tully, Vicki; Davey, Peter; Bell, Samira
Abstract: The National Institute for Health and Care Excellence (NICE) state that acute kidney injury (AKI) is seen in 13-18% of all people being admitted to hospital and that other patients will further go on to develop AKI during their time in hospital, with around 30-40% being in the operative setting. AKI has an estimated inpatient mortality of 20-30% in the UK and can lead to long-term morbidities like chronic kidney disease.[2] AKI is under-recognised and badly managed despite its prevalence and seriousness, with NCEPOD report stating that only 50% of patients with AKI received good care, that there was poor assessment of risk factors for AKI, and there was an unacceptable delay in recognising post-admission AKI in 43% of patients.[4] Baseline data collected on the urology ward in Ninewells Hospital, showed that only five of 22 (23%) patients undergoing urological surgery had post-operative creatinine measured on the ward within 48 hours (the primary method for detecting AKI). Excluding patients who were discharged the same day 5/16 (31%) received the blood test. The aim of the project was to increase the number of patients returning to ward 9 post-surgery who receive a serum creatinine measurement within two days of their urological surgery, excluding daycases. Specifically, we wanted the reliability of this measurement to be 95% or over in ward 9 by 30 July 2014. This was to be done by raising awareness around AKI on ward 9 and changing protocol so that every patient staying on ward 9 beyond their day of surgery should receive a post-operative creatinine. This would be tested for a set amount of time to see if patients with AKI were being missed. Despite not being able to implement a set protocol, the percentage of patients receiving post-operative creatinine measurements on ward 9 after a urological surgery still increased significantly. By interacting with the urology team and presenting our data, the knowledge and comprehension of the problem was altered. This lead to a change in culture and a significant increase in the number of post-operative creatinine measurements being taken. Through building relationships on the ward and sharing our data and knowledge there was an increase from 27% of patients receiving post-op creatinine in our first week of collecting data, to 87% in our last week on ward 9. However, without a set tool or change in protocol this change appears to have not been sustainable as the percentage dropped to 42% two weeks later.